Control method for phase-shift full-bridge center-tapped converters using a hybrid fuzzy sliding mode controller - Lee, Young Jae; Bak, Yeongsu; Lee, Kyo Beum (Electronics (Switzerland), 2019)
This paper presents a control method for phase-shift full-bridge center-tapped (PSFB-CT) converters using hybrid fuzzy sliding mode controllers (SMCs). Conventionally, the output voltage of a PSFB-CT converter is controlled by using a proportional-integral (PI) controller. However, the dynamic characteristic of the converter is undesirable, and the converter is not robust to disturbances. In order to overcome these disadvantages, the SMC based on PI control has been applied for the PSFB-CT converter. However, there is a chattering problem when the SMC gain is increased to improve the dynamic characteristic. In this paper, a control method for the PSFB-CT converter using fuzzy logic control is proposed. By varying the gain of the SMC through the fuzzy logic control, not only can the dynamic characteristic of the PSFB-CT converter be improved, but the chattering problem can also be relieved. The effectiveness of the proposed control method for the PSFB-CT converter was verified by the simulation and experimental results.
Keywords: Fuzzy logic control; Insulated DC/DC converter; Phase-shift full-bridge center-tapped (PSFB-CT) converter; Sliding mode controller (SMC)